Mom Blogging as Maternal Activism: How to Be an Ally for Autism Acceptance - Goldsmith, Daena J. (Journal of the Motherhood Initiative for Research and Community Involvement, 2021)
The autism acceptance movement advocates for respect, support, and accommodations so that autistics can participate in public life. This article examines two blogs by mothers of autistic children as case studies of how to be an ally to autism acceptance. In the early 2000s, the authors of Squidalicious and diary of a mom blogged about their experiences as mothers of autistic children who came to be advocates for autism acceptance. Dominant narratives of autism often portray it as a medical tragedy, and mothers of autistics are cast as warriors seeking cures or as martyrs to unfulfilling caregiving. In contrast, these blogs portray autism as a form of neurodiversity that includes both strengths and challenges, such as difficulties that come from social and physical environments that do not accommodate autism. By blogging about the everyday ups and downs of their lives, these mothers engage in five clusters of activity that constitute their allying with the autism acceptance movement: advocating for inclusion and accommodations; personalizing autism through portraying family life; providing social support for parents, children, and autistic advocates; educating readers about autism acceptance; and showing their own change and learning. Examining these practices in this specific context yields insight into the potential and challenges of online maternal activism.